2007
DOI: 10.1074/jbc.m609181200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Pool of Non-pumping Na/K-ATPase

Abstract: Recent studies have ascribed many non-pumping functions to the Na/K-ATPase. Here, we present experimental evidence demonstrating that over half of the plasma membrane Na/KATPase in LLC-PK1 cells is performing cellular functions other than ion pumping. This "non-pumping" pool of Na/K-ATPase, like the pumping pump, binds ouabain. Depletion of either cholesterol or caveolin-1 moves some of the "non-pumping" Na/KATPase into the pumping pool. Graded knock-down of the ␣1 subunit of the Na/K-ATPase eventually results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
258
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 228 publications
(273 citation statements)
references
References 49 publications
13
258
1
1
Order By: Relevance
“…However, the pumping activities in the I3 and F19 cells were much higher than that of parental PY-17 cells (19).…”
Section: Construction Of Cell Linesmentioning
confidence: 78%
“…However, the pumping activities in the I3 and F19 cells were much higher than that of parental PY-17 cells (19).…”
Section: Construction Of Cell Linesmentioning
confidence: 78%
“…Both PY-17 and C2-9 cells have disrupted Na/K-ATPase⅐c-Src signaling and do not respond to ouabain stimulation in terms of c-Src activation (11,31,32). As shown in Fig.…”
Section: Namentioning
confidence: 83%
“…94 Some studies have not found major differences in ouabain affinity between the caveolar and the non-caveolar Na + /K + -ATPase. 47 We have observed, however, that in renal proximal tubular epithelial cells both ouabain-induced signal transduction through the Na + /K + -ATPaseSrc-EGFR cascade and ouabain-induced clathrin-mediated endocytosis of the Na + /K + -ATPase were limited to the Na + /K + -ATPase residing in caveolae. 95,96 These discrepancies might be explained by different levels of expression of the γ subunit of the Na + /K + -ATPase in the preparations employed, as suggested by Nguyen and co-workers.…”
Section: Role Of Cardiotonic Steroids In Hypertension Endogenous Ouabainmentioning
confidence: 89%